The Effect of Audit Tenure, Invesment Opportunity Set and Accounting Conservatism Towards Earning Quality with Managerial Ownership As Moderating Variable - Zubaidah Zubaidah; Nasrizal Nasrizal (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This research aims to analyze the influence of audit tenure, investments opportunity set and the conservatism accounting to the quality of earning, as well as to know whether managerial ownership moderate relation between audit tenure, investment opportunity set and accounting conservatism towards the quality of earning. This research is a quantitative study using secondary data sourced from the company's financial statements published through the website https://www.idx.co.id. The population in this research were companies listed on the Indonesia stock exchange with a population target of LQ 45 company in 2015-2017. Sampling techniques used purposive sampling methods that produce as many as 23 company. Data processing used multiple linear regression analysis techniques and moderated regression analysis with the help of SPSS program version 22. The results showthat : 1).  Audit Tenure, Invesment Opportunity Set and accounting conservatism it affects the quality of earning; 2). Managerial ownership moderate the relationship between Audit tenure and accounting conservatism on earning quality; 3) Managerial ownership does not moderate the relationship between the Invesment Opportunity Set to the quality of earning